Developmental exposure to vasopressin increases aggression in adult prairie voles - Stribley, John M. (The National Academy of Sciences, 1999)
Although the biological roots of aggression have been the source of intense debate, the precise physiological mechanisms responsible for aggression remain poorly understood. In most species, aggression is more common in males than females; thus, gonadal hormones have been a focal point for research in this field. Although gonadal hormones have been shown to influence the expression of aggression, in many cases aggression can continue after castration, indicating that testicular steroids are not completely essential for the expression of aggression. Recently, the mammalian neuropeptide arginine vasopressin (AVP) has been implicated in aggression. AVP plays a particularly important role in social behavior in monogamous mammals, such as prairie voles (Microtus ochrogaster). In turn, the effects of social experiences may be mediated by neuropeptides, including AVP. For example, sexually naïve prairie voles are rarely aggressive. However, 24 h after the onset of mating, males of this species become significantly aggressive toward strangers. Likewise, in adult male prairie voles, central (intracerebroventricular) injections of AVP can significantly increase intermale aggression, suggesting a role for AVP in the expression of postcopulatory aggression in adult male prairie voles. In this paper, we demonstrate that early postnatal exposure to AVP can have long-lasting effects on the tendency to show aggression, producing levels of aggression in sexually naïve, adult male prairie voles that are comparable to those levels observed after mating. Females showed less aggression and were less responsive to exogenous AVP, but the capacity of an AVP V(1a) receptor antagonist to block female aggression also implicates AVP in the development of female aggression.